The cannabinoid receptor 1 associates with NMDA receptors to produce glutamatergic hypofunction: implications in psychosis and schizophrenia - Sánchez-Blázquez, Pilar; Rodriguez-Muñoz, María; Garzon, Javier (Frontiers in Pharmacology, 2014)
The endocannabinoid system is widespread throughout the central nervous system and its type 1 receptor (CB1) plays a crucial role in preventing the neurotoxicity caused by activation of glutamate N-methyl-D-aspartate receptors (NMDARs). Indeed, it is the activity of NMDARs themselves that provides the demands on the endogenous cannabinoids in order to control their calcium currents. Therefore, a physiological role of this system is to maintain NMDAR activity within safe limits, thereby protecting neural cells from excitotoxicity. Thus, cannabinoids may be able to control NMDAR overactivation-related neural dysfunctions; however the major obstacles to the therapeutic utilization of these compounds are their psychotropic effects and negative influence on cognitive performance. Studies in humans have indicated that abuse of smoked cannabis can promote psychosis and even circumstantially precipitate symptoms of schizophrenia, although the latter appears to require a prior vulnerability in the individual. It is possible that cannabinoids provoke psychosis/schizophrenia reflecting a mechanism common to neuroprotection the reduction of NMDAR activity. Cannabinoids are proposed to produce such effect by reducing the pre-synaptic release of glutamate or interfering with postsynaptic NMDAR-regulated signaling pathways. The efficacy of such control requires the endocannabinoid system to apply its negative influence in a manner that is proportional to the strength of NMDAR signaling. Thus, cannabinoids acting at the wrong time or exerting an inappropriate influence on their receptors may cause NMDAR hypofunction. The purpose of the present review is to draw the attention of the reader to the newly described functional and physical CB1-NMDAR association, which may elucidate the scenario required for the rapid and efficacious control of NMDAR activity. Whether alterations in these mechanisms may increase NMDAR hypofunction leading to vulnerability to schizophrenia will be outline